2018
DOI: 10.1007/978-3-319-58316-7_1
|View full text |Cite
|
Sign up to set email alerts
|

Musical Haptics: Introduction

Abstract: This chapter introduces to the concept of musical haptics, its scope, aims, challenges, as well as its relevance and impact for general haptics and humancomputer interaction. A brief summary of subsequent chapters is given. 1.1 Scope and Goals Musical haptics is an emerging interdisciplinary field investigating touch and proprioception in music scenarios from the perspectives of haptic engineering, humancomputer interaction (HCI), applied psychology, musical acoustics, aesthetics, and music performance. The go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…Though our work presented in this paper was not specifically focused on this type of feedback, a broad spectrum of time-based pneumotactile feedback can also be achieved with our control system and actuators by this control method, and could be leveraged to expand the tactile spectrum of an interface for specific application requirements, or dedicated data-physicalization [13] tasks in future work. Other approaches with similar types of tactile feedback have been demonstrated to convey various types of information [4,9,35], including audio data [15,24,26,34].…”
Section: Time-basedmentioning
confidence: 99%
“…Though our work presented in this paper was not specifically focused on this type of feedback, a broad spectrum of time-based pneumotactile feedback can also be achieved with our control system and actuators by this control method, and could be leveraged to expand the tactile spectrum of an interface for specific application requirements, or dedicated data-physicalization [13] tasks in future work. Other approaches with similar types of tactile feedback have been demonstrated to convey various types of information [4,9,35], including audio data [15,24,26,34].…”
Section: Time-basedmentioning
confidence: 99%
“…However, the relatively recent availability of affordable force and especially vibratory devices has brought to the foreground the effects that haptics have during performances [17]. Such effects have been shown to play a significant role, for instance, on the perception of quality in pianos [18] and violins [19], and the research field has gained enough relevance to become known as Musical Haptics [20].…”
Section: Haptic Feedbackmentioning
confidence: 99%
“…Musical Haptics is an emerging interdisciplinary field that focuses on investigating touch and proprioception in music scenarios from different perspectives [13]. Musical experiences involve both perceiving airborne acoustic waves and vibratory cues conveyed through air and solid media [13]. Traditional acoustic instruments intrinsically provide vibratory feedback during sound production.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that amplifying certain vibrations in a concert venue or music reproduction system can improve the musical experience [22], that vibrations play a significant role in the perception of music [23], and that whole-body vibrations (the type of haptic feedback used in the Sound Forest installation, see Section 2.1), can have a significant effect on loudness perception [24]. As pointed out in [13], musical haptics could potentially facilitate access to music for persons affected by somatosensory, visual, and hearing impairments. For example, haptic (or visual) feedback has been shown to enhance musical experiences for persons with hearing impairment [25].…”
Section: Introductionmentioning
confidence: 99%